Enchasing Production Planning and Inventory Management : A Quantitative Approachto Forecasting for Bottled Mineral Water Products at PT Arima - Sesar Husen Santosa; Agung Prayudha Hidayat; Annisa Rizkiriani; Khoirul Aziz Husyairi; Bayu Suriaatmaja Suwanda (Batrisya Education, 2024)
PT Arima is a company engaged in the production of bottled mineral water. The demand for bottled mineral water is experiencing fluctuations, with demand increasing at the end, so companies must carry out optimal production planning to avoid stock buildup. Production planning at PT Arima is carried out by identifying demand levels using quantitative forecasting methods, namely moving average (n = 3) and exponential smoothing (α = 0.05) to maintain optimal production levels and stock in the warehouse does not accumulate. The results of processing the level of forecasting accuracy using 12 months of demand data obtained using the moving average method showed that the production level = 39,733 boxes in January 2024. MAD = 3733.22; MSE = 21566024.78 and MAPE = 0.10. Based on the exponential smoothing method, the production level = 38,081 boxes in January 2024. MAD = 5773.50; MSE = 43466303 and MAPE = 0.15. Based on the results of comparing the MAPE values ​​of the two forecasting methods, the lowest MAPE value was obtained, namely the average method (n=3) of 0.10 with the production level of bottled mineral water to maintain optimal supply conditions in January 2024 of 39,733 boxes.